ANALISIS EFEKTIVITAS SISTEM INFORMASI AKADEMIK UNIVERSITAS NEGERI SURABAYA - Danella, Rikat (Jurnal Akuntansi AKUNESA, 2014)
Academic information system is a platform for users to search for information related to academic. As the development of technology information systems, information is becoming more available. Universitas Negeri Surabaya has implemented a web-based academic information system, so that users can easily find academic information. There are still deficiencies in the academic information systems of UNESA, with the improvement of these deficiencies is expected to help the users of academic information system to run effectively and efficiently.Keywords: academic information system, technology information system